Student Centered Learning Approaches; Learning Design Aqidah Morals For Government Elementary School - Muqarrahmah, Muqarramah (Tarbiyah : Jurnal Ilmiah Kependidikan, 2016)
Elementary School is a operational concrete time for young learners. Primary school curriculum exposing students to study Islamic education. In the Islamic primary school, students will study Islamic education and develop basic skills. Experience of students studying the Quran Hadith, Fiqh, Aqidah Akhlak, History and Practice of Islam and Arabic in schools should will build itself. Especially for Aqidah Akhlak are generally taught to the whole class, and it is the basis of the students in expressing religiosity. Learning Aqidah Akhlak have a great responsibility for the lives of students. Sometimes teachers teach Aqidah Akhlak using conventional method. This causes students to lose meaning in Islamic learning so that students just accept without critical dogma in it. The teacher becomes a source of knowledge and passive students in learning. The background of this analysis is Student Centered Learning approach; Aqidah Akhlak design learning for elementary Islam. Based Problems and paradigms in Aqidah Akhlak classes, Student Centered Learning approach can be developed that Cooperative Learning, Group Discussion, PBL, Connecting methods and Learning Differ can help teachers improve learning in primary school moral creed of Islam.